2017
DOI: 10.1515/pesd-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hail suppression operational programs on hail frequency and environment in Moldova

Abstract: Hailstorms pose a significant threat to all development sectors of the Republic of Moldova. Despite the availability of the intensive hail suppression operational programs the issues of their efficiency are very relevant for many years. In spite of expectations and previous claims the research findings show that the hail suppression activity in Moldova leads to increase of hail incidence rate (statistically tested at the 0.05 confidence level). Active influence on the hail formation processes has also environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Silver concentrations in waters were above 0.01 μg/L, which is the threshold proposed by Ratte (1999) for pristine areas. However, concentrations are significantly below the secondary standard threshold established by US EPA (2015) for silver (100 μg/L), as the ones obtained in Moldova (Potapov et al, 1996;and Cazac et al, 2017). Nevertheless, Cazac et al (2017) concluded that silver concentration in water pods in protected areas doubled the concentration of areas without hail suppression systems.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Silver concentrations in waters were above 0.01 μg/L, which is the threshold proposed by Ratte (1999) for pristine areas. However, concentrations are significantly below the secondary standard threshold established by US EPA (2015) for silver (100 μg/L), as the ones obtained in Moldova (Potapov et al, 1996;and Cazac et al, 2017). Nevertheless, Cazac et al (2017) concluded that silver concentration in water pods in protected areas doubled the concentration of areas without hail suppression systems.…”
Section: Discussionmentioning
confidence: 87%
“…However, silver concentration in waters from silver iodide used by hail suppression systems were not significant. In contrast, other studies car ried out in the same area, addressed that silver concentration in water reservoirs from protected areas doubled silver concentration in waters from control areas (Cazac et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…Federer et al, ; Knight et al, ), these hopes faded, though research toward the goal of hail suppression has persisted both regionally and in many parts of the globe (e.g. Cazac et al, ; Dessens et al, ; Farley et al, ; Gavrilov et al, ; Makitov et al, ; Wieringa & Holleman, ). Further details on these efforts can be found in Wieringa and Holleman () and Dessens et al ().…”
Section: Hailstone Ingredients Microphysics Physical Characteristicmentioning
confidence: 99%
“…Nonetheless, efforts to mitigate the impacts of hail continue to motivate a significant portion of hail research in southern and southeastern Europe (e.g. Cazac et al, ; Dessens et al, ; Gavrilov et al, ; Makitov et al, ; Wieringa & Holleman, ).…”
Section: Surface Observations Of Hailmentioning
confidence: 99%
“…In the Republic of Moldova, in an article about the efficiency of hail suppression (Potapov et al, 2007), it is stated the fact that the greatest number of hailstorms is recorded in the north and the higher lands of the central part of the country. Another study for Republic of Moldova (Cazac et al, 2017) shows that severe hail and an associated highimpactweather phenomena cause considerable damage mainly towards the environment, as well as to the agriculture, buildings, transport and infrastructure, yielding 50% of the total damage which is comparable to the drought impact.…”
Section: Introductionmentioning
confidence: 99%